Back Cover: Geometry‐Directed Self‐Assembly of Polymeric Molecular Frameworks (Angew. Chem. Int. Ed. 4/2021). Issue 4 (4th January 2021) - Yan, Xiao‐Yun; Guo, Qing‐Yun; Lin, Zhiwei; Liu, Xian‐You; Yuan, Jun; Wang, Jing; Wang, Haomin; Liu, Yuchu; Su, Zebin; Liu, Tong; Huang, Jiahao; Zhang, Ruimeng; et al.
Abstract : A solution‐processable thermally stable framework‐like material is reported by Zhiwei Lin, Stephen Z. D. Cheng, and co‐workers in their Communication on page 2024 . The highly ordered mesoporous structures are prepared from T‐shaped rod–sphere–polymer amphiphiles through selective decomposition of the polymer chains.